THE INFLUENCE OF HEALTH EDUCATION USING MEDIA E-BOOK ON NUTRITION FULFILLMENT KNOWLEDGE IN BREASTFEEDING MOTHERS - Nurul Azizah Jihad Fisabillillah; Gita Kostania; Herawati Mansur (SEAJOM: The Southeast Asia Journal of Midwifery, 2023)
One of the reasons for inadequate milk production is the lack of knowledge of mothers in understanding the importance of nutritional consumption during breastfeeding, this is due to a lack of information about nutritional consumption that affects the mother's diet. One of the efforts to increase mother's knowledge is by carrying out preventive efforts by providing health education, the component of the success of this effort is the use of media. E-book is a medium as well as a solution to make it easier to get knowledge. The purpose of this study was to determine the effect of health education using e-books on knowledge of nutritional fulfillment in breastfeeding mothers. This study used a pre-experimental design with a one group pretest posttest design approach. The research population is all mothers who have babies aged <6 months at PMB Indah Maharany Malang. The sampling technique used was purposive sampling with a total sample of 35 respondents. The research instrument used a questionnaire and an e-book. Data analysis used paired sample t-test. The statistical test results obtained a p value of 0.001 > 0.05, so it can be concluded that there is an effect of health education using e-books on knowledge of nutritional fulfillment in breastfeeding mothers at PMB Indah Maharany Malang. E-book media is a medium that is easy to understand, can be read whenever, the existence of e-books makes reading activities efficient and effective in fostering critical thinking skills. Based on the results of this study, it is necessary to provide health education using e-book media so that it can increase mother's knowledge in an effort to fulfill nutrition during breastfeeding.